THE USE OF ELECTRONIC STICK FIGURES FOR TEACHING WRITING RECOUNT TEXT TO THE EIGHT GRADE STUDENTS OF SMPN 2 WUNGU - Rara Wisna Sumiastari; Nuri Ati Ningsih; Rengganis Siwi Amumpuni (English Teaching Journal : A Journal of English Literature, Language and Education, 2017)
Writing English is considered as the most difficult skill among the other language skills (reading, speaking and listening). Therefore, it is important for the English teachers to find some creative ways to teach writing instead of only directing student to write without thinking how to facilitate them. Because of that reason, appropriate media is needed and should be used to help students master writing. Moreover, the use of multimedia in teaching and learning process is able to make the lesson become memorable and understandable. Therefore, Electronic stick figures in the form of multimedia are believed considerably suitable for teaching writing recount text. The result of this research show that the implementation of Electronic stick figures in teaching writing recount text are explaining material, introducing Electronic stick figures, and doing the task. Besides, advantages of Electronic stick figures in teaching writing are the use of Electronic Stick Figure can improve students’ learning process especially in writing, The Electronic Stick Figure is simple drwaing, Electronic Stick Figure helps the students to dig up their ideas and construct the text-type more easy, and the students very enthusiatic in a class.. Some disadvantages of the implementation of Electronic stick figuresare  teaching and learning using Electronick Stick Figure is not all class have a LCD, and the students still difficulties in past tense and some students’ vocabulary is lack, so that students less in making a good sentence.